Health implications of lower extremity amputations in Jordan: A retrospective analysis of demographic patterns and causes - Mahmoud Alfatafta; Nizar Alsubahi; Huda Alfatafta; Huthaifa Atallah; Amneh Alshawabka; Anthony McGarry; Alaeddin Ahmad (PLoS ONE, 2025)
Lower extremity amputation (LEA) is a significant health concern in Jordan, yet comprehensive data on its demographic and clinical characteristics remain limited. This retrospective analysis evaluated 893 LEA cases collected from Al-Basheer Hospital and six private prosthetic clinics in Amman between 2017 and 2023. Transtibial amputations (68.99%) were the most common, followed by transfemoral amputations (24.53%). Males were three times more likely than females to undergo LEA, with an overall mean age of 48.43 years (SD = 20.42). Diabetes mellitus (55.88%) was the leading cause, followed by cancer (18.48%) and trauma (11.65%). Age and cause were significantly associated (p < 0.01); DM-related amputations were more prevalent among older adults (mean age 62.04 years). The findings highlight that TT amputations in older males with diabetes represent the most common LEA profile in Jordan. Targeted public health initiatives including diabetic foot care education, early detection, and regular screenings, are urgently needed to reduce LEA incidence in the country.